Comparison of the Occlusal Feature Index (OFI) and Dental Aesthetic Index (DAI) in 10–14-year-old children at the Universitas Sumatera Utara Dental Hospital - Hilda Fitria Lubis; Arfah Azriana (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Malocclusion often occurs in children due to discrepancies between primary teeth and permanent teeth. An assessment of the severity of the malocclusion is necessary for establishing the diagnosis and determining the need for treatment. The Occlusal Feature Index (OFI) and Dental Aesthetic Index (DAI) are indices that assess the need for orthodontic treatment, but they use different weights. Purpose: This study aimed to compare the need for orthodontic treatment based on the OFI and DAI in 10–14-year-old children. Methods: The sample in this study is secondary data in the form of 66 study models pre-treatment in children aged 10–14 years at the Universitas Sumatra Utara (USU) Dental Hospital. All samples were collected based on inclusion and exclusion criteria. The measurement results were analysed statistically by the Chi-square test to see the comparison between the OFI and DAI. The results obtained are presented in the form of frequency and percentage. Results: For the OFI, 42.4% of the samples had no orthodontic treatment needed, 31.8% were indicated to treat, and 25.8% require mandatory treatment. For the DAI, 47% of samples had no/little treatment need, 25.8% had elective treatment need, 16.7% had treatment considered mandatory, and 10.6% treatment highly desirable. Based on the assessment to compare the OFI and DAI using the Chi-square test, p=0.001 was obtained. Conclusion: There was a significant difference in the need for orthodontic treatment between OFI and DAI in children aged 10–14 years at the USU Dental Hospital.